6 Minute Walk Test (6MWT) for Healthy Adult Volunteers - Syed Muarraf Hussain, Faizania Tausif, Nauman Aziz, Syed Mukarram Hussain (Journal of Rawalpindi Medical College, 2021)
Objectives: To determine the 6-minute walk test (6MWT) for healthy volunteers in our population and find out the factors affecting 6MWT. Furthermore, comparing our results with published National and International data. Study Design: Cross-sectional study. Place and Duration of Study: This study was carried in the physiology department of Rawalpindi Medical College, from 1st July 2019 to 31st December 2019. Materials and Methods: A total of 129 adult healthy volunteers between 18 and 60 years of age were included in this study after the application of inclusion and exclusion criteria. A 6-minute walk test (6MWT) was carried out in a standardized procedure. The height, weight, and BMI were recorded on predesigned Performa. Distance covered in 6-minute, heart rate, systolic BP, Diastolic BP, SPO2, Borg Scale Dyspnea score, Borg Scale Fatigue score were recorded before and after the 6-minute walk test. Correlation and its significance were calculated among anthropometric and physiological variables. Results: Seventy (54%) men and Fifty-nine (46%) women participated in the study. The mean distance covered for all subjects was 430.412±63.0150. The distance covered by the female subject was 388.720±30.104 and 439.533±68.355 by male subjects. The mean age of the subjects was 31.64 ±12.36, while the mean BMI was 22.06 ±4.15. The mean heart rate value before the test is 77.72±1.48 and after the test is 92.84±1.12. The mean systolic BP value before the walk was 122.65±11.75 and after the walk, it was 106.5±9.83. Mean diastolic BP before the walk was 80.55±12.61 and after the walk, it was 76.5±9.83. SPO2 mean value before the walk was 96.23±1.4 and after the walk is 98.2±1.17. Borg scale dyspnea score mean value before the test is 0 ± 0 and after the test it was 0.67±0.76 and Borg scale fatigue score mean value before the walk is 1.32±0.73 and after the walk is 1.62±0.92. A positive correlation was noted with height, while a negative correlation was noted with age and BMI. Gender also showed a significant relationship with the 6MWD. Conclusion: The distance covered in 6-minute is shorter than the studies carried out in different parts of the world. Age, gender, height, and BMI showed a significant relationship with 6MWD. Those reference values for the 6MWD should not be used in our population, as it overestimates the distance and may interfere with the significance of the test.